A first insight into the production of bone, antler and tooth objects at the Copper and Bronze Age site of Fulgeriş – La trei cireşi - Țerna, A.; Istina, L. (Materiale și Cercetări Arheologice)
Artefacts from bone, antler and wild boar tusk were recovered from both Copper Age and Bronze Age contexts during the archaeological excavations at the site of Fulgeriș– La trei cireşi, between 2004 and 2013. The intention of this study is to offer a first characterization of the manufacturing process and to build up a classification based on morpho-functional and technological criteria. The assemblages are composed mainly of domestic equipment and one can observe a clear preference towards the exploitation of bone over tusks and antler. Due to the larger size of the Copper Age collection one can recognize the use of various methods of blank production : fracturing, bi-, quadri-and multi-partitioning, sectioning, while for the Bronze Age only fracturing and partitioning were identified. With few exceptions, the assemblage shows a low degree of elaboration, where shaping plays a marginal role in the transformation of the blanks